MODAL SOSIAL DAN DUKUNGAN SOSIAL TERHADAP KINERJA USAHA IWAPI PROVINSI SULAWESI SELATAN - Suyuthi, Nurmadhani Fitri (Patria Artha Management Journal, 2019)
This study aims to review and discuss the literature on social capital and social support for business performance (IWAPI, South Sulawesi Province). On this basis, a hypothetical model as a basis for theoretical and hypothetical development is further reviewed. Social capital owned by women is influenced by values and norms regarding trust, moral values, namely norms and networks of interaction between family and environment that support women entrepreneurs in developing their business. Social support is a source of emotional, informational or mentoring provided by people around individuals to deal with every problem in life. This form of support can be in the form of information, certain behavior, or material that can make individuals who receive assistance be supported, motivated and valuable. Women in entrepreneurship need support from their families and the environment which makes women have independence in entrepreneurship. The population in this study were 212 women entrepreneurs IWAPI South Sulawesi. Samples were determined as many as 183 respondents.Keywords: Social Capital, Social Support, Business Performance